Occupational stress in nursing professionals of a university hospital - Lucas Carvalho Santana; Lúcia Aparecida Ferreira; Lenniara Pereira Mendes Santana (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: To identify the presence of occupational stress in nursing professionals of a university hospital in the inlands of the state of Minas Gerais and examine influence of sociodemographic and occupational characteristics in this disease. Methods: Cross-sectional, exploratory and quantitative study with 124 professional nurses from a university hospital in the inlands of the state of Minas Gerais. The adapted and validated Portuguese version of the Job Stress Scale (JSS) was used for the performance of the study. Results: Most professionals were women (87.9%) with a mean age of 40.2 years, 80.6% were nursing technicians and 71.8% of the sample had some degree of exposure to occupational stress. Conclusions: The occupational stress index was higher than that observed in previous studies. Data obtained in the study point to the need to implement institutional measures for the prevention of occupational stress, especially by strengthening social support at work.